TRF2 Controls Telomeric Nucleosome Organization in a Cell Cycle Phase-Dependent Manner - Galati, Alessandra; Magdinier, Frédérique; Colasanti, Valentina; Bauwens, Serge; Pinte, Sébastien; Ricordy, Ruggero; Giraud-Panis, Marie-Josèphe; Pusch, Miriam Caroline; Savino, Maria; Cacchione, Stefano; Gilson, Eric (PLOS ONE, 2012)
Mammalian telomeres stabilize chromosome ends as a result of their assembly into a peculiar form of chromatin comprising a complex of non-histone proteins named shelterin. TRF2, one of the shelterin components, binds to the duplex part of telomeric DNA and is essential to fold the telomeric chromatin into a protective cap. Although most of the human telomeric DNA is organized into tightly spaced nucleosomes, their role in telomere protection and how they interplay with telomere-specific factors in telomere organization is still unclear. In this study we investigated whether TRF2 can regulate nucleosome assembly at telomeres. By means of chromatin immunoprecipitation (ChIP) and Micrococcal Nuclease (MNase) mapping assay, we found that the density of telomeric nucleosomes in human cells was inversely proportional to the dosage of TRF2 at telomeres. This effect was not observed in the G1 phase of the cell cycle but appeared coincident of late or post-replicative events. Moreover, we showed that TRF2 overexpression altered nucleosome spacing at telomeres increasing internucleosomal distance. By means of an in vitro nucleosome assembly system containing purified histones and remodeling factors, we reproduced the short nucleosome spacing found in telomeric chromatin. Importantly, when in vitro assembly was performed in the presence of purified TRF2, nucleosome spacing on a telomeric DNA template increased, in agreement with in vivo MNase mapping. Our results demonstrate that TRF2 negatively regulates the number of nucleosomes at human telomeres by a cell cycle-dependent mechanism that alters internucleosomal distance. These findings raise the intriguing possibility that telomere protection is mediated, at least in part, by the TRF2-dependent regulation of nucleosome organization.